Method for calculating fractal dimension of bonding surface of geopolymer repair material and existing concrete

Through the calculation method of fractal dimensions of the bonding surface of ground polymer repair materials and existing concrete, the problem of bonding performance being affected by various factors is solved, the morphological characteristics of bonding surfaces are quantitatively characterized, the bonding performance is optimized, and the repair effect is improved and structural durability.

CN119205874APending Publication Date: 2024-12-27ZHENGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411248082.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

In concrete restoration projects, the bonding performance between the ground polymer restoration material and existing concrete is affected by a variety of factors. How to ensure good bonding is the key, especially the interface roughness, bonding angle and concrete strength are greatly affected. This causes the bonding surface to become the weakest part, affecting the carrying capacity and durability of the overall structure.

Method used

The fractal dimension calculation method of the bonding surface of the ground polymer repair material and existing concrete surface is used to prepare concrete matrix test pieces, process bonding surfaces, conduct shear bonding tests, test three-dimensional morphology and calculate fractal dimensions to quantify the bonding surfaces. Topomorphic characteristics, optimized bonding performance.

Benefits of technology

Through the fractal dimension calculation method, the roughness and complexity of the bonding surface can be accurately reflected, providing an important basis for evaluating the bonding performance between the ground polymer repair materials and existing concrete, helping to select appropriate repair materials and optimize construction technology, and improving Repair effect and structural service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119205874A_ABST
    Figure CN119205874A_ABST
Patent Text Reader

Abstract

The invention discloses a fractal dimension calculation method for a bonding surface of a geopolymer repair material and existing concrete, and relates to the technical field of building materials. Comprising the following steps: preparing a concrete matrix test piece; treating the bonding surface of the concrete matrix, and measuring the roughness of the bonding surface; preparing a repairing test piece; carrying out a shear bonding test; testing the three-dimensional shape of the failure surface, and quantitatively characterizing the shear bonding performance of the high geopolymer concrete and the existing concrete interface; calculating the fractal dimension of the three-dimensional curved surface; through point cloud data analysis of a three-dimensional scanning system, the three-dimensional morphology characteristics of the bonding surface of the shear test piece are explored. The method provided by the invention is helpful for realizing quantitative characterization of interface shear bonding performance of high-strength geopolymer concrete (HSGC) and existing concrete (OPCC).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to a method for calculating the fractal dimension of a bonding surface between a geopolymer repair material and existing concrete. Background Art

[0002] Geopolymer is a three-dimensional zeolite network structure formed by polymerization such as excitation and lattice reconstruction with natural minerals, solid wastes and synthetic compounds rich in silicon and aluminum as raw materials. Geopolymer has the characteristics of fast hardening speed, good impact resistance, high temperature resistance and excellent acid and alkali resistance. A large amount of fly ash, slag and other wastes are used in the preparation process, which reduces energy consumption and three wastes and has obvious environmental benefits. Therefore, the application of alkali excitation technology, the development of high-strength geopolymer repair materials, the addition of mixed fibers to improve the shortcomings of geopolymer materials, and the advantages of high-strength geopolymer concrete play an important role in improving the integrity of reinforced hydraulic concrete structures and extending their service life. In addition, the compatibility between the repair material and ordinary concrete must also be considered. Compared with the concrete matrix and the repair material, the interface is the weakest part of the repaired concrete. When the concrete structure is under load, cracks are easy to occur and expand from the interface, which directly leads to the cracking and destruction of the entire concrete. Therefore, the interface phase determines the macroscopic properties of the concrete structure to a large extent. Geopolymers are widely used in the field of building materials due to their excellent mechanical properties, acid and alkali resistance, fire resistance and high temperature resistance. Especially in concrete repair projects, geopolymer materials have attracted much attention due to their good bonding properties and durability. However, the bonding performance between geopolymers and existing concrete is affected by many factors, including interface roughness, bonding angle, concrete strength, etc. Damage repair of concrete structures has always been a hot topic and difficulty in research. For existing concrete structures, how to effectively improve their bearing capacity and durability is an urgent problem to be solved. As a new type of repair material, geopolymer repair materials have broad application prospects. However, in practical applications, how to ensure good bonding between geopolymer repair materials and existing concrete is the key. With the continuous development of computer technology, computational science is increasingly widely used in the fields of materials science and water conservancy engineering. Through numerical simulation and computational analysis, the performance and structural characteristics of materials can be studied more deeply, providing strong support for material design and engineering applications. Computational science also plays an important role in the calculation of the fractal dimension of the bonding surface between geopolymer repair materials and existing concrete. By adopting appropriate calculation methods and algorithms, the fractal dimension of the bonding surface can be accurately calculated, providing an important basis for evaluating the bonding performance between geopolymer repair materials and existing concrete.

[0003] In practical applications, how to ensure good bonding between geopolymer repair materials and existing concrete interfaces is the key. With the continuous development of computer technology, computational science is increasingly used in the fields of materials science and water conservancy engineering. Through numerical simulation and computational analysis, the performance and structural characteristics of materials can be studied more deeply, providing strong support for material design and engineering applications. Computational science also plays an important role in the calculation of the fractal dimension of the bonding surface between geopolymer repair materials and existing concrete. By adopting appropriate calculation methods and algorithms, the fractal dimension of the bonding surface can be accurately calculated, providing an important basis for evaluating the bonding performance between geopolymer repair materials and existing concrete.

[0004] Therefore, how to provide a method for calculating the fractal dimension of the bonding surface between geopolymer repair materials and existing concrete, and quantitatively characterize the morphological characteristics of the bonding surface between geopolymer repair materials and existing concrete through the fractal dimension calculation method, is a problem that technical personnel in this field urgently need to solve. Summary of the invention

[0005] In view of this, the present invention provides a method for calculating the fractal dimension of the bonding surface between a geopolymer repair material and existing concrete, which can achieve quantitative characterization of the shear bonding performance of the interface between HSGC and OPCC.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] A method for calculating the fractal dimension of the bonding surface between a geopolymer repair material and existing concrete comprises the following steps:

[0008] S1. Prepare concrete matrix specimens;

[0009] S2. Treat the bonding surface of the concrete substrate and measure the roughness of the bonding surface;

[0010] S3, preparing repaired specimens;

[0011] S4. Conduct shear bond test;

[0012] S5. Test the three-dimensional morphology and quantitatively characterize the shear bonding performance of the interface between high-strength geopolymer concrete and existing concrete;

[0013] S6, calculating the fractal dimension of the three-dimensional surface;

[0014] S7. Through the point cloud data analysis of the three-dimensional scanning system, the three-dimensional morphological characteristics of the bonding surface of the substrate specimen are explored.

[0015] The above method, optionally, includes the following steps in S1:

[0016] S101, preparing a test mold for a molded test piece of a preset size;

[0017] S102, loading the prepared concrete mixture into the test mold in S101 in layers, vibrating it, smoothing the casting surface, and applying a plastic wrap;

[0018] S103, after being placed at room temperature for a preset time, the mold is removed, numbered, and the molded specimen is moved to a standard curing room for curing;

[0019] S104, taking out the molded test piece.

[0020] In the above method, optionally, S2 includes the following contents:

[0021] The concrete matrix bonding surface is divided into type I bonding surface, type II bonding surface, type III bonding surface and type IV bonding surface;

[0022] Type I bonding surface is an untreated smooth surface, which is used as the reference group for comparative analysis;

[0023] Type II bonding surface adopts steel brush brushing method, which is carried out after the concrete matrix is ​​poured;

[0024] The treatment method for type III bonding surface is a combination of steel brushing and deep chiseling. After the concrete matrix is ​​poured, the surface is first brushed; the middle area of ​​the interface is chiseled;

[0025] The type IV bonding surface is a natural cleavage surface.

[0026] The above method can be optionally used to measure the roughness of the bonding surface by sand filling method, and the average depth of sand filling is:

[0027]

[0028] Among them, H is the average depth of sand filling, in mm; V is the volume of sand filling, in mm 3 ; A is the bonding surface area, unit is mm 2 ;

[0029] In the above method, optionally, S3 includes the following:

[0030] The concrete matrix specimens were cured in a curing room for a preset time, immersed in water for a preset time, and placed in a triple steel mold for casting after the surface was dry. The types of repair materials were grouped and numbered.

[0031] In the above method, optionally, S5 includes the following contents:

[0032] The bonding surface of the concrete specimen before pouring and the failure surface after the shear bonding test were scanned in three dimensions, and the morphological characteristic parameters and fractal dimension of the bonding surface were calculated. The fractal dimension of the interface was calculated using the cubic box covering method.

[0033] In the above method, optionally, the concave-convex interface is projected onto the plane XOY, and divided into a square grid with a side length of δ, and the four corner points (i, j), (i, j+1), (i+1, j), (i+1, j+1) of the grid correspond to the four heights h(i, j), h(i, j+1), h(i+1, j), h(i+1, j+1) on the interface respectively; the concave-convex interface is covered with a cube with a side length of δ, and the number of cubes N(i, j) covering the area δ×δ is calculated as:

[0034]

[0035] Among them, INT is the rounding function;

[0036] The total number of cubes required to cover the entire measured area is N δ for:

[0037]

[0038] Among them, n and m are the number of measurement points in the X and Y axis directions respectively;

[0039] If the concave-convex interface has fractal properties, the total number of cubes N δ There should be the following relationship between δ and scale:

[0040]

[0041] Where D is the fractal dimension of the concave-convex interface.

[0042] The above method can be used to evaluate the three-dimensional topographic characteristics of the bonding surface of the shear specimen. The main parameters are the maximum height difference of the profile H d , outline area ratio S r and the volume V from the contour surface to the center plane l ;

[0043] Maximum height difference of profile H d The maximum peak height H of the surface profile in the shear plane p and the maximum valley depth H v The distance between them is calculated as:

[0044] H d =H p -H v ;

[0045] Outline area ratio S r is the expanded area of ​​the contour surface in the shear plane S d and shear surface area S a The ratio is calculated as:

[0046] S r =S d / Sa ;

[0047] Profile surface development area S d and the volume V from the contour surface to the center plane l Acquired via Geomagic Studio software.

[0048] It can be seen from the above technical solution that, compared with the prior art, the present invention provides a method for calculating the fractal dimension of the bonding surface between a geopolymer repair material and existing concrete, which has the following beneficial effects:

[0049] 1) The morphological characteristics of the bonding surface between geopolymer repair materials and existing concrete can be quantitatively characterized by the fractal dimension calculation method. As an important parameter for describing the complexity and structural characteristics of irregular patterns, the fractal dimension can accurately reflect the roughness and complexity of the bonding surface, providing an important basis for evaluating the bonding performance between geopolymer repair materials and existing concrete.

[0050] 2) According to the calculated fractal dimension, the bonding performance between different geopolymer repair materials and existing concrete can be evaluated, which is helpful to select appropriate repair materials and optimize construction technology in actual projects, thereby improving the repair effect and quality;

[0051] 3) By optimizing the bonding performance between geopolymer repair materials and existing concrete, the repair effect can be improved and the service life of the repaired concrete structure can be extended, which is of great significance for ensuring project safety and reducing maintenance costs;

[0052] 4) The research and application of this calculation method will help promote scientific research and technological development in fields such as materials science, water conservancy engineering and computational science. Through continuous in-depth research, the calculation method can be further improved, the calculation accuracy and efficiency can be improved, and strong support can be provided for scientific research and technological innovation in related fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0054] Figure 1 A flow chart of a method for calculating the fractal dimension of a bonding surface between a geopolymer repair material and existing concrete disclosed in the present invention;

[0055] Figure 2 A physical picture of a concrete base mold disclosed in an embodiment of the present invention;

[0056] Figure 3 A physical picture of a concrete matrix specimen disclosed in an embodiment of the present invention;

[0057] Figure 4 This is an example diagram of bonding surface types of shear test pieces disclosed in an embodiment of the present invention;

[0058] Figure 5 A physical picture of a three-dimensional scanner disclosed in an embodiment of the present invention;

[0059] Figure 6 An example diagram of a test piece disclosed in an embodiment of the present invention;

[0060] Figure 7 Physical pictures and three-dimensional morphology pictures of shear specimens with different bonding surface types disclosed in the embodiments of the present invention;

[0061] Figure 8 Log(N δ ) and Log(δ) fitting curve diagram;

[0062] Fig. 9 A schematic diagram of fractal dimensions of bonding interfaces with different roughness disclosed in an embodiment of the present invention;

[0063] Fig.10 A statistical diagram of the correlation between the fractal dimension and the roughness disclosed in the embodiment of the present invention;

[0064] Fig.11 This is a diagram of a shear bonding test device disclosed in an embodiment of the present invention. DETAILED DESCRIPTION

[0065] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0066] In this application, relational terms such as first and second, etc. are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. The terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of more restrictions, the elements defined by the sentence "comprise one..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0067] Reference Figure 1 As shown, the present invention discloses a method for calculating the fractal dimension of the bonding surface between a geopolymer repair material and existing concrete, comprising the following steps:

[0068] S1. Prepare concrete matrix specimens;

[0069] S2. Treat the bonding surface of the concrete substrate and measure the roughness of the bonding surface;

[0070] S3, preparing repaired specimens;

[0071] S4. Conduct shear bond test;

[0072] S5. Test the three-dimensional morphology and quantitatively characterize the shear bonding performance of the interface between high-strength geopolymer concrete and existing concrete;

[0073] S6, calculating the fractal dimension of the three-dimensional surface;

[0074] S7. Through the point cloud data analysis of the three-dimensional scanning system, the three-dimensional morphological characteristics of the bonding surface of the substrate specimen are explored.

[0075] Specifically, the concrete matrix strength grade (C30, C40, C50 and C60), bonding surface type (Ⅰ, Ⅱ, Ⅲ and Ⅳ) and PVA fiber content (0%, 0.3%, 0.6%, 0.9% and 1.2%) in high-strength geopolymer concrete (HSGC) were used as three factor levels to explore the influence of different variables on the shear bond performance between HSGC and existing concrete (OPCC). When exploring the influence of PVA fiber on the bond performance between HSGC and OPCC, the steel fiber content was set to 1%. At the same time, when exploring the influence of concrete matrix strength grade and interface type on the bond performance between HSGC and OPCC, the PVA fiber and steel fiber content in HSGC were set to 0.6% and 1%, respectively. The specific test plan is shown in Table 1.

[0076] Table 1 Shear bond test scheme

[0077]

[0078] Among them, in C30R2P0.6, C30 means that the concrete matrix strength grade is C30, R2 means that the interface type is type II, and P0.6 means that the PVA fiber content is 0.6% and the steel fiber content is 1%.

[0079] Furthermore, S1 includes the following steps:

[0080] S101, preparing a test mold for a molded test piece of a preset size;

[0081] S102, loading the prepared concrete mixture into the test mold in S101 in layers, vibrating it, smoothing the casting surface, and applying a plastic wrap;

[0082] S103, after being placed at room temperature for a preset time, the mold is removed, numbered, and the molded specimen is moved to a standard curing room for curing;

[0083] S104, taking out the molded test piece.

[0084] Specifically, refer to Figure 2 As shown, the test mold of the molded specimen uses a triple steel mold with a size of 100mm×100mm×50mm. The prepared concrete mixture is loaded into the test mold in layers and vibrated, and then the casting surface is smoothed with a spatula, and finally covered with plastic wrap. After being placed at room temperature for 24 hours, the mold is removed, the specimen is numbered, and the specimen is moved to a standard curing room (temperature of 20±2℃, relative humidity of 95%) for curing. The curing age is 3 months, and then the concrete matrix specimen is taken out to cast another part of the repair material.

[0085] Furthermore, S2 includes the following contents:

[0086] The concrete matrix bonding surface is divided into type I bonding surface, type II bonding surface, type III bonding surface and type IV bonding surface;

[0087] Type I bonding surface is an untreated smooth surface, which is used as the reference group for comparative analysis;

[0088] Type II bonding surface adopts steel brush brushing method, which is carried out after the concrete matrix is ​​poured;

[0089] The treatment method for type III bonding surface is a combination of steel brushing and deep chiseling. After the concrete matrix is ​​poured, the surface is first brushed; the middle area of ​​the interface is chiseled;

[0090] The type IV bonding surface is a natural cleavage surface.

[0091] Specifically, the bonding surface size is 100mm×100mm, and the interface type after treatment is as follows: Figure 4 As shown. Type I bonding surface is an untreated smooth surface, which is used as the reference group for comparative analysis. Type II bonding surface adopts the steel brush brushing method, which is brushed 2 days after the concrete matrix is ​​poured. If the pouring time is too long, the steel brush brushing method is difficult to operate, and only the surface of the specimen can be lightly treated. In order to keep the roughness of the specimens under the same working condition consistent, the brushing time of all specimens is 3 minutes. The treatment method of type III bonding surface is a combination of steel brush brushing method and deep chiseling method. After 2 days of concrete matrix pouring, the surface is first brushed for 3 minutes; then, in order to prevent serious damage to the edge of the interface, only the middle area of ​​the interface (60mm×60mm) is chiseled. Type IV bonding surface is a natural split surface. The roughness of this method varies greatly, so six specimens are used in each group for shear bonding test.

[0092] Furthermore, the roughness of the bonding surface was measured by the sand filling method, and the average depth of the sand filling was:

[0093]

[0094] Among them, H is the average depth of sand filling, in mm; V is the volume of sand filling, in mm 3 ; A is the bonding surface area, unit is mm 2 ; Calculation shows that the roughness of bonding surfaces of types Ⅰ, Ⅱ, Ⅲ and Ⅳ are 0mm, 0.45mm, 2.21mm and 8.10mm respectively.

[0095] Furthermore, S3 includes the following:

[0096] The concrete matrix specimens were cured in a curing room for a preset time, immersed in water for a preset time, and placed in a triple steel mold for casting after the surface was dry. The types of repair materials were grouped and numbered.

[0097] Specifically, after three months of curing, the concrete matrix is ​​taken out of the curing room and soaked in water for 24 hours before pouring the HSGC repair material. After the surface is dry, it is placed in a triple steel mold (100mm×100mm×100mm) for pouring the HSGC part. Figure 3 As shown, there are 6 groups of restoration material types, which are numbered P0S0, P0, P0.3, P0.6, P0.9 and P1.2 respectively.

[0098] Specifically, refer to Fig.11As shown in S4, this embodiment adopts the Z-type shear test method. The test device is composed of two parts of steel molds that are symmetrical and completely identical. Screw holes are reserved on the left and right sides of the steel mold to fix the displacement meter, and a pressure sensor is placed on the upper side of the steel mold. The test adopts a 100kN electro-hydraulic servo universal testing machine for loading. The loading method is displacement control and the loading rate is 0.1mm / min. Since most of the shear specimens are brittle fractures, in order to collect the descending section of the shear load-displacement curve as much as possible, this test uses a dynamic data acquisition instrument to record the displacement and load transmitted by the displacement meter and pressure sensor, and the acquisition frequency is 50Hz. During the test, it is necessary to observe the crack development process and failure morphology of the specimen, and record the failure load.

[0099] Furthermore, S5 includes the following contents:

[0100] The bonding surface of geopolymer concrete specimens before pouring and the failure surface after shear bonding test were scanned in three dimensions, and the morphological characteristic parameters and fractal dimension of the bonding surface were calculated. The fractal dimension of the interface was calculated using the cubic box covering method.

[0101] Specifically, the shear bonding performance of the HSGC and OPCC interface is quantitatively characterized. The 3D scanning system includes a HandySCAN 3D handheld scanner and 3D scanning software. The 3D scanner and the shear specimen to be tested are as follows: Figure 5 , Figure 6 As shown. The interface size is 100mm×100mm, the measurement interval is 0.25mm, and the data points obtained are about 16,000. The point cloud data (.asc) is imported into Geomagic Studio software for editing. After packaging, the shear bonding specimen model is generated, and the shear specimen morphological characteristic parameters are obtained. Subsequently, the point cloud file is imported into Python to read the coordinate data, and the three-dimensional surface model is reconstructed and the fractal dimension is calculated based on the self-written program.

[0102] Furthermore, the concave-convex interface is projected onto the plane XOY and divided into a square grid with a side length of δ. The four corner points (i, j), (i, j+1), (i+1, j), and (i+1, j+1) of the grid correspond to the four heights h(i, j), h(i, j+1), h(i+1, j), and h(i+1, j+1) on the interface respectively. The concave-convex interface is covered with a cube with a side length of δ, and the number of cubes N(i, j) covering the area δ×δ is calculated as:

[0103]

[0104] Among them, INT is the rounding function;

[0105] The total number of cubes required to cover the entire measured area is N δ for:

[0106]

[0107] Among them, n and m are the number of measurement points in the X and Y axis directions respectively;

[0108] If the concave-convex interface has fractal properties, the total number of cubes N δ There should be the following relationship between δ and scale:

[0109]

[0110] Where D is the fractal dimension of the concave-convex interface.

[0111] Furthermore, the parameters for evaluating the three-dimensional morphological characteristics of the bonding surface of the shear specimen mainly include the maximum height difference of the profile H d , outline area ratio S r and the volume V from the contour surface to the center plane l ;

[0112] Maximum height difference of profile H d The maximum peak height H of the surface profile in the shear plane p and the maximum valley depth H v The distance between them is calculated as:

[0113] H d =H p -H v ;

[0114] Among them, the bottom of the bonding specimen is used as the reference surface, and the maximum height difference of the profile only measures the height of the shear surface, without considering the specific profile changes on the shear surface.

[0115] Outline area ratio S r is the expanded area of ​​the contour surface in the shear plane S d and shear surface area S a The ratio is calculated as:

[0116] S r =S d / S a ;

[0117] Profile surface development area S d and the volume V from the contour surface to the center plane l Acquired via Geomagic Studio software.

[0118] Specifically, the physical pictures and three-dimensional morphology of shear specimens with different bonding surface types are as follows: Figure 7As shown, by comparing the original bonding surface images, it is found that the morphological features of the two surfaces are highly consistent, indicating that the numerically reconstructed image can better restore the morphological features of the fracture surface of the shear specimen. This embodiment further explores the three-dimensional morphological features of the bonding surface of the shear specimen through point cloud data analysis of the three-dimensional scanning system.

[0119] Specifically, the contour surface development area S d and the volume V from the contour surface to the center plane l The calculation process is to first import the point cloud data; then delete the isolated points and non-connected points in vitro, and then delete the useless points outside the sheared sample and perform noise processing; secondly, generate a polygonal model and edit the model, including boundary repair, hole repair, and deletion of overlapping parts; finally, calculate the sum of all meshes of the shear surface of the model and integrate the shear surface to obtain the contour surface expansion area S d and the volume V from the contour surface to the center plane l . Contour area ratio S r and the volume V from the contour surface to the center plane l It can reflect the roughness of the shear surface. The closer the contour area ratio is to 1, the smoother the shear surface is, and vice versa. The larger the volume from the contour surface to the center plane, the rougher the shear surface is.

[0120] The three-dimensional scanning data of the shear bonding specimens were calculated and analyzed to obtain the three-dimensional morphological parameters of the bonding specimens before and after shearing, as shown in Table 2. Before shearing, the maximum height differences of the contours of the type I, II, III and IV shear bonding specimens were 0.00 mm, 1.89 mm, 4.36 mm and 12.49 mm, respectively; after shearing, the maximum height differences of the contours of the type I, II, III and IV shear bonding specimens were 4.90 mm, 8.97 mm, 10.54 mm and 19.83 mm, respectively. The maximum height difference of the contours of the specimens after shearing was greater than that before shearing. The normalized results showed that the ratio of the maximum height difference of the contours before and after shearing gradually decreased with the increase of the interface roughness. Before shearing, the contour area ratios of type I, II, III and IV shear bond specimens were 1.00, 1.03, 1.07 and 1.17, respectively; after shearing, the contour area ratios of type I, II, III and IV shear bond specimens were 1.01, 1.02, 1.09 and 1.15, respectively. The contour area ratio of type I shear bond specimens after shearing was greater than that of the specimens before shearing, and the contour area ratios of the specimens after shearing of other interfaces were all smaller than those before shearing. The ratio of the contour area ratios of the specimens before and after shearing after normalization ranged from 0.975 to 1.020, indicating that there was no significant change in the contour area ratio of the specimens before and after shearing. For the volume from the contour surface to the center plane, before shearing, the volumes from the contour surface to the center plane of type I, II, III and IV shear bond specimens were 0.00 mm, respectively. 3 , 4.54e 3 mm 3 , 8.28e 3 mm 3 and 3.59e 4 mm 3 ; After shearing, the volume from the contour surface to the center plane of type I, II, III and IV shear bond specimens is 1.63e 3 mm 3 , 5.85e 3 mm 3 , 9.37e 3 mm 3 and 3.46e 4 mm 3 The results show that the interface roughness of type Ⅰ, Ⅱ and Ⅲ shear bond specimens after shearing is greater than that before shearing, while the volume from the contour surface to the center plane of type Ⅳ shear bond specimen has no obvious change before and after shearing.

[0121] Table 2 Three-dimensional morphology parameters of shear surface

[0122]

[0123] Specifically, the calculation of the fractal dimension of the fracture bonding surface based on the cubic box covering method is crucial for a better understanding of the morphological characteristics of the interface. The fractal dimension of the type I bonding cross section calculated based on fractal theory is as follows: Figure 8 As shown in the figure, Log(N δ ) and Log(δ) have a high linear correlation, that is, the scale δ in fractal geometry is related to the corresponding total number of cubes N. δ The relationship between the fracture bond surface and the fracture bond surface indicates that the fracture bond surface is a fractal structure and can be characterized by the fractal dimension. The three-dimensional data of shear bond surfaces with different roughness are processed by fractal geometry theory, and the fractal dimension of each bond surface is calculated by the slope of the straight line in the double logarithmic coordinates. Fig. 9 The results show that with the increase of roughness, the fractal dimension of type I, II, III and IV interfaces also gradually increases. It can be seen that the fractal dimension can better characterize the roughness of the interface between HSGC and OPCC, which is convenient for quantitative analysis between different interfaces.

[0124] Specifically, refer to Fig.10 As shown in the figure, the correlation between the fractal dimension and roughness of different bonding surfaces and the fitting curve. It can be seen from the figure that the roughness is closely related to the fractal dimension. When the roughness is less than 2.0 mm, the fractal dimension increases significantly with the increase of roughness; when the roughness is greater than 2.0 mm, the fractal dimension gradually tends to be flat with the increase of roughness. The results show that when the roughness is not greater than 2.21 mm, increasing the interface roughness can effectively improve the interfacial bonding performance between HSGC and OPCC. Therefore, the fractal dimension can be used to characterize the interface roughness of concrete, and the repair effect between HSGC and OPCC can be roughly inferred, avoiding the deviation caused by traditional interface treatment and evaluation methods, making the interface treatment more reasonable and standardized. The results show that roughness is closely related to fractal dimension. When the roughness is less than 2.0 mm, the fractal dimension increases significantly with the increase of roughness. When the roughness is greater than 2.0 mm, the fractal dimension gradually tends to be flat with the increase of roughness. When the roughness is not greater than 2.21 mm, increasing the interface roughness can effectively improve the interfacial bonding performance between HSGC and OPCC.

[0125] In order to clearly illustrate the interchangeability of hardware and software, the above description has generally described the components and steps of each example according to function. Whether these functions are performed in hardware or software depends on the specific application and design constraints of the technical solution. Professional and technical personnel can use different methods to implement the described functions for each specific application, but such implementation should not be considered beyond the scope of the present invention.

[0126] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for calculating the fractal dimension of the bonding surface between a geopolymer repair material and existing concrete, characterized in that: The following steps are involved: S1. Prepare concrete matrix specimens; S2. Treat the bonding surface of the concrete substrate and measure the roughness of the bonding surface; S3, preparing repair specimens; S4. Conduct shear bond test; S5. Test the three-dimensional morphology and quantitatively characterize the shear bonding performance of the interface between high-strength geopolymer concrete and existing concrete; S6, calculating the fractal dimension of the three-dimensional surface; S7. Through the point cloud data analysis of the 3D scanning system, the 3D morphological characteristics of the bonding surface of the substrate specimen are explored.

2. The method for calculating the fractal dimension of the bonding surface between a geopolymer repair material and existing concrete according to claim 1, characterized in that: S1 includes the following steps: S101, preparing a test mold for a molded test piece of a preset size; S102, loading the prepared concrete mixture into the test mold in S101 in layers, vibrating it, smoothing the casting surface, and applying a plastic wrap; S103, after being placed at room temperature for a preset time, the mold is removed, numbered, and the molded specimen is moved to a standard curing room for curing; S104, taking out the molded test piece.

3. The method for calculating the fractal dimension of the bonding surface between a geopolymer repair material and existing concrete according to claim 1, characterized in that: S2 includes the following: The concrete matrix bonding surface is divided into type I bonding surface, type II bonding surface, type III bonding surface and type IV bonding surface; Type I bonding surface is an untreated smooth surface, which is used as the reference group for comparative analysis; Type II bonding surface adopts steel brush brushing method, which is carried out after the concrete matrix is ​​poured; The treatment method for type III bonding surface is a combination of steel brushing and deep chiseling. After the concrete matrix is ​​poured, the surface is first brushed; the middle area of ​​the interface is chiseled; The type IV bonding surface is a natural cleavage surface.

4. The method for calculating the fractal dimension of the bonding surface between a geopolymer repair material and existing concrete according to claim 3, characterized in that: The roughness of the bonding surface is measured by the sand filling method. The average depth of the sand filling is: Among them, H is the average depth of sand filling, in mm; V is the volume of sand filling, in mm 3 ; A is the bonding surface area, unit is mm 2 .

5. The method for calculating the fractal dimension of the bonding surface between a geopolymer repair material and existing concrete according to claim 1, characterized in that: S3 includes the following: The concrete matrix specimens were cured in a curing room for a preset time, immersed in water for a preset time, and placed in a triple steel mold for casting after the surface was dry. The types of repair materials were grouped and numbered.

6. The method for calculating the fractal dimension of the bonding surface between a geopolymer repair material and existing concrete according to claim 1, characterized in that: S5 includes the following: The bonding surface of the concrete specimen before pouring and the failure surface after the shear bonding test were scanned in three dimensions, and the morphological characteristic parameters and fractal dimension of the bonding surface were calculated. The fractal dimension of the interface was calculated using the cubic box covering method.

7. The method for calculating the fractal dimension of the bonding surface between a geopolymer repair material and existing concrete according to claim 6, characterized in that: Project the concave-convex interface onto plane XOY and divide it into a square grid with a side length of δ. The four corner points of the grid (i, j), (i, j+1), (i+1, j), (i+1, j+1) correspond to the four heights h(i, j), h(i, j+1), h(i+1, j), h(i+1, j+1) on the interface respectively. Cover the concave-convex interface with a cube with a side length of δ, and calculate the number of cubes N(i, j) covering the area δ×δ as follows: Among them, INT is the rounding function; The total number of cubes required to cover the entire measured area is N δ for: Among them, n and m are the number of measurement points in the X and Y axis directions respectively; If the concave-convex interface has fractal properties, the total number of cubes N δ There should be the following relationship between δ and scale: Where D is the fractal dimension of the concave-convex interface.

8. The method for calculating the fractal dimension of the bonding surface between a geopolymer repair material and existing concrete according to claim 1, characterized in that: The parameters for evaluating the three-dimensional morphological characteristics of the bonding surface of the shear specimen mainly include the maximum height difference of the profile H d , outline area ratio S r and the volume V from the contour surface to the center plane l ; Maximum height difference of profile H d The maximum peak height H of the surface profile in the shear plane p and the maximum valley depth H v The distance between them is calculated as: H d =H p -H v ; Outline area ratio S r is the expanded area of ​​the contour surface in the shear plane S d and shear surface area S a The ratio is calculated as: S r =S d / S a ; Profile surface development area S d and the volume V from the contour surface to the center plane l Obtained through Geomagic Studio software.